2022
DOI: 10.1111/cas.15529
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor receptor 3 overexpression mediates ALK inhibitor resistance in ALK‐rearranged non–small cell lung cancer

Abstract: The rearrangement of anaplastic lymphoma kinase (ALK) occurs in 3%‐5% of patients with non–small cell lung cancer (NSCLC) and confers sensitivity to ALK–tyrosine kinase inhibitors (TKIs). For the treatment of patients with ALK‐rearranged NSCLC, various additional ALK‐TKIs have been developed. Ceritinib is a second‐generation ALK‐TKI and has shown great efficacy in the treatment of patients with both newly diagnosed and crizotinib (a first‐generation ALK‐TKI)‐refractory ALK‐rearranged NSCLC. However, tumors can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Other described bypass resistance mechanisms include activation of FGFR2&3 and cMET. 29 Interestingly, previous studies have identified and receptor tyrosine kinases (RTK), such as FGFR2, can act as an upstream activator of ERBB3. 30 In addition, metabolic reprogramming of 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (PFKFB3) via STAT3 has recently been linked to ALK TKI resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Other described bypass resistance mechanisms include activation of FGFR2&3 and cMET. 29 Interestingly, previous studies have identified and receptor tyrosine kinases (RTK), such as FGFR2, can act as an upstream activator of ERBB3. 30 In addition, metabolic reprogramming of 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (PFKFB3) via STAT3 has recently been linked to ALK TKI resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the onset of acquired resistance is a common event and dramatically Pace et al Journal of Translational Medicine (2023) 21:626 hampers therapeutic efficacy [63]. FGFR signaling pathways have been described as molecular mechanisms for acquired resistance to TKIs targeting other tyrosine kinase receptors, such as EGFR, c-Met, ALK and CDK4/6 [64][65][66]. Although functional studies are needed, the evidence that pemigatinib treatment can modulate other TKI targets reinforces the biological rationale for combinatorial strategies to overcome TKI resistance and improve clinical benefit.…”
Section: Discussionmentioning
confidence: 99%
“…FGFR3 spans 16.5 kb with 18 introns and 19 exons and is situated on chromosome 4p16.3. FGFR3 is a member of the FGFR family and has been found to regulate cell growth, cell differentiation, and migration ( 16 , 17 ). FGFR3 is involved in a variety of biological processes including cell proliferation, differentiation, migration, angiogenesis, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…FGFR3 spans 16.5 kb with 18 introns and 19 exons and is situated on chromosome 4p16.3. FGFR3 is a member of the FGFR family and has been found to regulate cell growth, cell differentiation, and migration (16,17).…”
Section: Introductionmentioning
confidence: 99%